Lubricant Distribution Process From Sales to Consumers - Widyaningrum , Aprilia; Evy Purwitasari, Maria (International Publisher, 2022)
The purpose of this study was to determine the lubricant distribution process, to determine the constraints in the lubricant distribution process, to find solutions that can be applied in overcoming the lubricant distribution constraints. The research methodology used is descriptive qualitative which aims to describe the conditions and analyze the Lubricant Distribution Process. In this study, data related to the author's study are sourced from library studies, field studies, and documentation techniques. The results of the research regarding the lubricant distribution process, the authors draw the following conclusions: the lubricant distribution process has several stages as follows: The customer visits the office or sends a PO (Purchase Order) to the Sales team. Then the CS (Customer Service) Team helps the sales team schedule shipments by inputting data according to customer requests into the system. The process of checking data, goods and prices is carried out by the Sales Spv to provide a decision on whether or not the goods and prices will be sold and sent to the customer. If the PO is approved or approved by SPV Sales, the issuance of a travel certificate will appear in the distribution system, but if the PO is not approved, the travel document will not be printed and the price quote will be reviewed to the customer. Constraints in the Lubricant Distribution Process are as follows: lack of delivery fleets, lack of driver discipline, and inappropriate delivery of goods to customers. The solutions are: adding inventory (Distribution Fleet) as needed, giving warnings, guidance, coaching and direction to drivers both inside and outside the company, and accepting returned goods according to company policies and procedures.